Uso da ventilação de volume alvo: conhecimento de fisioterapeutas e médicos atuantes em unidades de terapia intensiva neonatal - Alixandra Wellingta Ferreira da Silva; Adisson Lucas Albuquerque Maranhão; Rafael Justino da Silva (Universidade de Pernambuco, 2021)
Objective: To evaluate the knowledge of the professional who deals directly with mechanical ventilatory assistance in relation to the target volume modalities. Method: This is a transversal, quantitative study with the application of a questionnaire with direct questions about the modality, 24 professionals participated among physiotherapists and doctors working in the Neonatal Intensive Care Unit of Barão de Lucena Hospital, between October 2019 and January 2020. Results: We identified that only 62.5% of the professionals received training for the modality, 33.3% felt able to use it and only 50% would know how to proceed with weaning. When asked about the benefits 87.5% believe in positive outcomes for neonatal population, 100% would put in practice after training. Conclusion: The questionnaire allowed a critical analysis about the modality and the professionals working in the neonatal ICU, evidencing that with the training we will have capable professionals in the administration of the modality and clinical and subjective improvement of these patients.